Evidence of a nanosized copper anodic reaction in an anaerobic sulfide aqueous solution. Issue 24 (17th February 2016) - Zhang, Bowei; Hao, Shiji; Wu, Junsheng; Li, Xiaogang; Huang, Yizhong
Abstract : The present paper reports the use of TEM to investigate the electrochemical behavior of copper subject to the both free corrosion and polarization in sulfide aqueous solution at nano scale. Abstract : The present paper reports the use of TEM to investigate the electrochemical behavior of a copper subject to the both free corrosion and polarization in a 0.1 M NaCl + 5 × 10 −4 M Na2 S aqueous solution at the nano scale. The pure copper is found to be transformed into nano-crystalline Cu2 S in the thin region of the copper needle in the solution at open circuit conditions. However, a rough Cu2 S layer is formed in the active region of electrochemical polarization, which is then converted to the passive CuS layer with a uniform thickness at higher potentials. Upon the continuous increase of an applied potential, cubic CuS particles with sizes of ∼100 nm are precipitated on the needle surface due to the breakdown of the passive layer. Meanwhile, the growth of a large amount of nanosized CuCl particles is also found, indicating that Cl − ions participate in the electrochemical reaction in the transpassive region. It is worth noting that the present work also provides a simple and cost-effective way for the synthesis of copper sulfides (Cu2 S and CuS) through electrochemical processes.